Population aging and corporate tax avoidance: Suppression or promotion? - Luzhuang Qi; Peng Liang (PLoS ONE, 2025)
Addressing population aging has emerged as a paramount national strategic priority. Against the backdrop of a continual rise in population aging and considerable escalation in labor costs within China, this study aims to investigate whether firms, confronted with the burden of labor costs, intensify their tax avoidance motives to generate a “stimulating effect” or whether they are compelled to adapt traditional factors, thereby reducing tax avoidance and exerting a “restraining effect”. To address this inquiry, we empirically examine the impact of population aging on corporate tax avoidance and its underlying mechanisms utilizing a sample of non-financial listed companies in China’s A-share market spanning from 2008 to 2023. Our findings substantiate that the level of population aging significantly diminishes firms’ tax avoidance motives, confirming the presence of a “restraining effect”. Mechanism tests unveil that population aging, through capital-labor substitution, fosters research and development innovation and improves production efficiency, thus curbing firms’ tax avoidance behavior and affirming the existence of the “factor substitution effect” “innovation capacity effect” and “resource allocation effect”. Heterogeneity analysis reveals that the inhibitory impact of population aging on corporate tax avoidance is more pronounced in labor-intensive industries, entities with limited financing capacity, weak financial conditions, and adverse external financial conditions. By examining the economic ramifications of population aging from a micro-level perspective on corporate financial decision-making and enriching the existing literature on corporate tax avoidance through a population economics lens, this study provides valuable insights for firms undergoing transformation and informs policy formulation in response to the challenges posed by population aging.